Visible-light-induced perfluoroalkylation/arylmigration/desulfonylation cascades of conjugated tosyl amides. Issue 4 (25th January 2017) - Tang, Shi; Yuan, Li; Deng, You-Lin; Li, Zeng-Zeng; Wang, Liang-Neng; Huang, Gui-Xiu; Sheng, Rui-Long
Graphical abstract: Highlights: General route toward oxindoles bearing various perfluorinated moieties. Novel visible-light induced desulfonyaltion carbo-perfluoroalkylation. Using comparatively low cost Rf I as fluorine sources. Mild reaction conditions and broad substrate scope. Abstract: An effective visible-light-induced perfluoroalkylation of conjugated tosyl amides using R f -X (X = I or Br) as the R f source by Ir photocatalyst was disclosed. This protocol provides a new way to prepare oxindoles or α -aryl- β -fluoroalkyl amides bearing various perfluorinated moieties such as n -C3 F7, i -C3 F7, n -C4 F9, n -C6 F13, n -C8 F17, n -C10 F21 and CF2 CO2 Et.